Комментарий к трудовому кодексу Российской Федерации (постатейный) постатейный - Смирнов О. В. Олег Владимирович; Буянова М. О.; Костян И. А.; Малов В. Г. (Москва, КноРус, 2010)
Исключено из фонда НТБ ТПУ